ความสมมูลของอสมการแปรผันและรูปแบบไฟไนท์เอลิเมนต์ของปัญหาสิ่งกีดขวางสำหรับเชือกยืดหยุ่น (The Equivalence of Variational Inequality and Finite Element Formulation of the Obstacle Problem for a String) - สิรินิลกุล, พิศุทธวรรณ ศรีภิรมย์ (Science Essence Journal, 2012)
การศึกษาความสมมูลของอสมการแปรผันและการสร้างรูปแบบไฟไนท์เอลิเมนต์ของปัญหาสิ่งกีดขวางในหนึ่งมิตินี้ได้ทำการศึกษาผ่านปัญหาเส้นลวดไร้น้ำหนักซึ่งถูกแทนที่ด้วยวัตถุชิ้นหนึ่งโดยปัญหาดังกล่าวเป็นปัญหาทางกายภาพอย่างง่ายที่นำไปสู่แนวคิดเชิงคณิตศาสตร์ของการสร้างอสมการแปรผัน เริ่มจากการพิจารณาปัญหาทางกายภาพเพื่อสร้างปัญหาเชิงเส้นแล้วจะได้ปัญหาอสมการแปรผันจากการพิจารณาปัญหาค่าน้อยสุด ในที่สุด รูปแบบไฟไนท์เอลิเมนท์โดยใช้ฟังก์ชันฐานหลักแบบเชิงเส้นจะถูกสร้างขึ้นภายในปริภูมิไฟไนท์เอลิเมนท์ The equivalence of variational inequality and finite element formulation of one dimensional obstacle problem is observed thru the weightless elastic string which is displaced by a body. This is a simple physical problem which will lead to the mathematical idea of a variational inequality formulation. The physical problem is firstly introduced in order to formulate a complementary problem. The variational inequality is then obtained by considering the minimization problem of the energy involving to elastic deformation. Finally, the finite element approximation with linear basis function to variational inequality over the finite element space is presented.